Protocol for development and validation of an Early Intervention device and its influence using STructured Early Physiotherapy (PreemieSTEP) Intervention on Neuromotor Development in Preterm Infants - Indira D B Naidu Boddapati; Sivakumar Gopalakrishnan; Sonia Khurana; Jayashree Purkayastha; Bhaskar Bhatt; Bhamini Krishna Rao (MethodsX, 2025)
Early physiotherapy interventions for Moderate to Late Preterm (MLP) infants often lack continuity of care from hospital to home settings. This research aims to develop an Early Intervention (EI) device for home program and determine its influence using STructured Early Physiotherapy (Preemie STEP) intervention in MLP infants. For phase I, qualitative interviews will be conducted with healthcare professionals and parents, to understand user needs on developed prototype. Based on identified needs, an EI device will be developed using a human-centered design approach and iterative design process. In phase II, usability and validity of EI device will be evaluated on 10 infants to assess its appropriateness and ease. Further, a pilot Randomized Control Trial (RCT) will be conducted on 24 MLP infants using Preemie STEP intervention in which EI device will be incorporated as a tool to facilitate home program. Treatment includes from Neonatal Intensive Care Unit (NICU) which constitutes Movement Imitation Therapy (MIT) and followed by a home program using the developed EI device from post-hospital discharge to 6 months follow-up. Data collected will be analyzed using thematic for qualitative interviews and descriptive for usability and feasibility outcomes. Clinical effectiveness will be analyzed using repeated measures ANOVA or Friedman's test.